A Comparison of Co-methylation Relationships Between Rheumatoid Arthritis and Parkinson's Disease - Tang, Guoping; Pan, Hongzhi; Xu, Liangde; Feng, Rennan; Jiang, Yongshuai; Kong, Fanwu; Hu, Simeng (Frontiers in Neuroscience, 2019)
Rheumatoid arthritis (RA) is a complex autoimmune disease. Recent studies have identified the DNA methylation loci associated with RA and found that DNA methylation was a potential mediator of genetic risk. Parkinson’s disease (PD) is a common neurodegenerative disease. Several studies have indicated that DNA methylation levels are linked to PD, and genes related to the immune system are significantly enriched in PD-related methylation modules. Although recent studies have provided profound insights into the DNA methylation of both RA and PD, no shared comethylation relationships have been identified to date. Therefore, we sought to identify shared comethylation relationships linked to RA and PD. Here, we calculated the Pearson’s correlation coefficient (PCC) of 225,239,700 gene pairs and determined the differences and similarities between the two diseases. The global comethylation change between in PD cases and controls was larger than that between RA cases and controls. We found 337 gene pairs with large changes that were shared between RA and PD. This comethylation relationship study represents a new area of study for both RA and PD and provides new ideas for further study of the shared biological mechanisms of RA and PD.